Prognostic factors in aneurysmal subarachnoid hemorrhage during the clazosentan era: a multicenter study using multivariate analyses and machine learning model - Muraoka, Shinsuke; Izumi, Takashi; Ishii, Kazuki; Takeuchi, Issei; Nishihori, Masahiro; Goto, Shunsaku; Kanamori, Fumiaki; Uda, Kenji; Sakamoto, Yusuke; Yokoyama, Kinya; Nishida, Kazuki; Chrétien, Basile; et al. (Neurosurgical Review, 2025)
BACKGROUND: Controlling delayed cerebral ischemia (DCI) is crucial for improving the prognosis in patients with aneurysmal subarachnoid hemorrhage (aSAH). This study aimed to identify prognostic factors in patients with aSAH in Japan. METHODS: A multicenter, retrospective, observational cohort study was conducted from April 2021 to March 2024. Patients underwent surgical repair of ruptured aneurysms within 48 h of onset, followed by postoperative treatment with multiple drugs, including clazosentan and fasudil, to prevent cerebral vasospasm. The primary outcome was the proportion of patients with a good outcome, defined as a modified Rankin Scale score of 0 to 2 at discharge. Multivariate logistic regression and stepwise model selection were applied to identify prognostic factors. SHapley Additive exPlanations (SHAP) analysis was used to visualize the relative importance of predictors and their impact on outcomes. RESULTS: Among 506 patients (mean age 63.5 years, 66.6% female), 53.0% achieved a favorable outcome. In multivariate analysis, treatment with clazosentan was associated with 1.84 times higher odds of a favorable outcome (p = 0.021), increasing to 1.97 when clazosentan was administered without fluid retention complications (p = 0.010). SHAP analysis further highlighted the impact of each factor on prognosis, identifying a lower WFNS grade, lower Fisher grade, younger age, clazosentan, cilostazol, and statin use as significant predictors of favorable outcomes. CONCLUSION: Clinical status at aSAH onset and age are uncontrollable factors; therefore, improving prognosis requires targeted prevention of DCI and effective management of brain edema. The administration of therapies such as clazosentan, cilostazol, and statins may contribute to favorable outcomes. CLINICAL TRIAL NUMBER: Not applicable.